ANALYSIS OF THE EFFECT OF NON PERFORMING LOAN AND LIQUIDITY ON PROFITABILITY IN BANKING SECTOR COMPANIES PERIOD 2017 – 2021 - Tanujaya, Jessicha; Kurniawan, Cindy; Spanic, Vincent; Khairani, Rafida (ZILLZELL MEDIA PRIMA, 2023)
This study supposed to examine and analyze the effect of non performing loan and liquidity on profitability in banking sector companies for the period 2017-2021. The research method used in this study uses quantitative research methods with descriptive quantitative research types that are explanatory research. The population of this study is the entire banking sector companies listed on the Indonesia Stock Exchange amounted to 46 companies, the sample of this study as many as 20 companies with purposive sampling sampling technique. The method of data analysis used is multiple linear regression. The results of the F test research where F counts 8.215 > F table 3.09 with a significant level of 0.001 < 0.05 show that simultaneously bad loans and liquidity have a significant effect on profitability in banking sector companies listed on the Indonesia Stock Exchange for the period 2017-2021. The results of the t test where only bad loans that have a positive and significant effect on profitability while the remaining liquidity has no effect on profitability. The results of the analysis of the coefficient of determination obtained Adjusted R2 value of 0.174, meaning that the variable variation of bad debts and liquidity is equal to 17.4%, while the remaining 82.6% is explained by other variables.